DIAGENESIS OF THE CRETACEOUS SANDSTONE IN YUYANG FORMATION OF JIANGHAN BASIN AND ITS THERMODYNAMIC ANALYSE - Guan P.; Zhang W.T.; Wu X.S.; Xong J.Y. (My University, 2006)
Sandstones diagenesis in the Cretaceous Yuyang Formation, Jianghan Basin, China is charactered by cementation and replacement. Optical microscopy and other petrological studies have revealed four main diagenetic events. They include early carbonate cementation (mainly dolomite), secondary growth of Fe-dolomite, anhydrite cementation and replacement and a phase of late carbonate (mainly calcite) cementation and replacement. Thermodynamic modeling has been used to analyse the evolution of the geochemical environment during diagenesis. CaO, MgO, H2O, SO2 and CO2 were considered as major components in a closed diagenetic system. Thermodynamic phase diagrams of the five-component system were calculated, in order to understand the controlling factors and processes. Under certain restricted conditions extracted from measured data, assemblages of mineral phases appearing in each diagenetic event were compared with the phase diagrams. It could be shown that the pH of the solution plays an important role in the diagenesis process. Cementation and replacement of carbonates (both, calcite and dolomite) were caused by a higher pH, while the cementation and replacement of anhydrite occurred at lower pH conditions. For example, acidification of pore fluids by intrusion of organic acids as a result of oil migration leads to a cementation and replacement of anhydrite. The influence of the concentrations of related ions (Ca2+, Mg2+, CO32-, SO42-) in the solution on the diagenetic processes, will also be discussed.
Keywords: ANHYDRITE; CALCITE; DIAGENESIS; DOLOMITE; THERMODYNAMIC PHASES DIAGRAMS; Мезозой::Меловая; Mesozoic::Cretaceous